Water use and conservation in the operating room and perioperative setting: A scoping review - Nicholas Kramer; Jay Zhu; Maya Xolal Herzig; Duncan Alexander Meiklejohn (PLoS ONE, 2026)
Public health and food security in the United States depend on a reliable supply of fresh water. Freshwater availability is worsening, and prolonged drought conditions have affected large portions of the country. Hospitals are major consumers of water, and processes related to the operating room may present an opportunity to improve water conservation. A scoping review of the MEDLINE, Science Citation Index-Expanded, Emerging Sources Citation Index, and Embase databases was conducted for articles addressing water use and interventions for water conservation from January 1, 1948, to March 26, 2025. The review identified twenty-six studies meeting inclusion criteria, addressing four subsets of operating room and perioperative processes. The preponderance of published studies addressed water use during surgical hand scrubbing, with the remainder evaluating water use related to textiles, equipment, or sterilization processes. Interventions supported by high-quality evidence for reducing water use included turning off idling sterilizer equipment when not in use. Moderate to low quality evidence favored converting to waterless scrub techniques and/or on-demand scrub sinks, reusable alternatives for equipment, and non-cotton reusable textiles. Our findings identify several focused areas with potential for improving water conservation in the operative and perioperative setting. Further research is needed to comprehensively evaluate operating room, perioperative and overall hospital processes for water use, and to describe effective interventions for conservation.